Greater presence of receptors for relaxin in the ligamentum teres of female infants who undergo open reduction for developmental dysplasia of the hip - BOZKURT, SÜHEYLA (BMC, 2021)
Background: While many factors involved in the etiology of developmental dysplasia of the hip (DDH), one of which is the hormone relaxin. Relaxin concentrations in patients with DDH may lead to pathodynamic changes during hip development by altering the physiological nature of the ligament, as well as by long-term exposure to relaxin during pregnancy. Our objective in this study was to determine the number of relaxin receptors in the ligamentum teres and their role in causing DDH. Methods: We identified 26 infants between birth and 3 years of age who had undergone open reduction for DDH between 2010 and 2012. 12 hips of 12 miss abortus fetus between 20 to 35 weeks of gestation were used as control group. Specimens obtained from two groups were stained with Relaxin-2 antibody, and the amount of staining for relaxin receptors was determined using an ordinal H score. Results: The mean (SD) H scores of infants with DDH were significantly higher than those of controls: 215 (59) versus 52 (48); P = 0.00; 95% CI. Statistically significant difference between the two groups in terms of gender was not found. Conclusion: As a result, increased number of relaxin receptors in the ligamentum teres could be a risk factor for DDH.
Keywords: SERUM RELAXIN; MECHANICAL-PROPERTIES; EXPRESSION; TRANSMISSION; ASSOCIATION; STABILITY; PREGNANCY; ISOFORMS; COLLAGEN; HORMONE